(untitled) - Peter Varhol (South Carolina, U.S.A, 1997)
Excutive summary; State-of-th-Art Technology; Web server requirements; Considering theoperating system; Considering the operating system; the sun solution; Intel's alternative; What about the mainframe; Other web server platforms...
Keywords: client/server computing,internet